2005
DOI: 10.1007/s00122-005-0109-x
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature adult-plant (HTAP) stripe rust resistance gene Yr36 from Triticum turgidum ssp. dicoccoides is closely linked to the grain protein content locus Gpc-B1

Abstract: Several new races of the stripe rust pathogen have become frequent throughout the wheat growing regions of the United States since 2000. These new races are virulent to most of the wheat seedling resistance genes limiting the resistance sources that can be used to combat this pathogen. High-temperature adult-plant (HTAP) stripe rust resistance has proven to be more durable than seedling resistance due to its non-racespecific nature, but its use is limited by the lack of mapping information. We report here the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 215 publications
(146 citation statements)
references
References 25 publications
3
138
0
5
Order By: Relevance
“…Three-QTL controlled HTAP resistance was reported in wheat cultivar Express [52]. In addition, the recently cloned Yr36, a single-gene or QTL conditioning HTAP resistance was reported in wheat genotypes transgressed from Triticum dicoccoides [31,32]. Similarly, the Yr18 conditioning stripe rust resistance we considered as HTAP resistance was also recently cloned as the same gene as Lr34 for durable resistance to leaf rust [60].…”
Section: Genetics Of Htap Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Three-QTL controlled HTAP resistance was reported in wheat cultivar Express [52]. In addition, the recently cloned Yr36, a single-gene or QTL conditioning HTAP resistance was reported in wheat genotypes transgressed from Triticum dicoccoides [31,32]. Similarly, the Yr18 conditioning stripe rust resistance we considered as HTAP resistance was also recently cloned as the same gene as Lr34 for durable resistance to leaf rust [60].…”
Section: Genetics Of Htap Resistancementioning
confidence: 99%
“…The 2-way testing would include high-temperature resistance, which also expresses in the seedling stage, but may eliminate plants with adult-plant resistance expressing only at low temperatures. The recently cloned Yr36 was classified as HTAP resistance based the 2-way testing [31], but was late identified more accurately as temperature-sensitive resistance using the 4-way testing [32]. Under field conditions, temperature-sensitive resistance mainly express in the adult-plant stage because temperatures are usually low in the early crop season, which does not allow high-temperature resistance to express.…”
Section: Determination Of Htap Resistancementioning
confidence: 99%
“…The natural habitats of T. dicoccoides are located in the Middle East Fertile Crescent. T. dicoccoides populations harbor a valuable pool of resistance genes that can be transferred into cultivated wheat (Rong et al 2000;Knott et al 2005;Mergoum et al 2005;Uauy et al 2005;Marais et al 2005;Gustafson et al 2009). Numerous studies of T. dicoccoides genetic diversity have shown that the population in…”
Section: Morris 2006) In Wild Emmer Wheat (T Dicoccoides) Populatiomentioning
confidence: 99%
“…The Canada Western Hard White (CWHW) class was introduced in 2001 to accommodate market opportunities for white-seeded wheat with end-use suitability more similar to CWRS, and launched with the cultivars Snowbird (Humphreys et al 2007b) Winter hexaploid wheat (T. aestivum L.) differs from spring wheat by genes that control response to a vernalization requirement (Worland and Snape 2001) and generally for cold tolerance (Fowler and Gusta 1979;Thomas et al 1988). Winter wheat has been grown in Canada from the early 1600s by settlers in Atlantic Canada and Quebec and represents the majority of the wheat production in eastern Canada.…”
Section: Wheat Production In Western Canadamentioning
confidence: 99%
“…Resistance to stripe rust has been incorporated into some of the CWSWS cultivars, such as AC Reed (Sadasivaiah et al 1993), since they were developed for production in southwest Alberta. Most cultivars in the other classes are relatively susceptible, except for those that carry Lr34 and the completely linked stripe rust resistance gene Yr18 and Yr36 linked to Gpc-B1 (Uauy et al 2005).…”
Section: Important Traits In Western Canadianmentioning
confidence: 99%